2020
DOI: 10.2147/jaa.s279916
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Prevalence of Allergic Rhinitis and Associated Risk Factors Among University Students in Anatolia</p>

Abstract: Introduction Allergic rhinitis is a common disease in Turkey. However, there are not enough studies on its prevalence. Survey-based studies conducted by experienced and qualified researchers to large populations provide information about the prevalence of allergic rhinitis and risk factors associated with it. Aim The aim of this study was to determine the prevalence of allergic rhinitis and related factors in university students in Anatolia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…The risk of childhood asthma in infants living in the highest urbanization level was higher than that in infants residing in the lowest urbanization level (OR, 1.26; 95% CI, 1.24–1.29; p < 0.0001). In a previous study, the risk of asthma or AR is higher in children living in rural areas than in urban areas ( 25 ). The lower prevalence of childhood asthma in children living in farms is associated with asthma-protective “farm effect” ( 26 ).…”
Section: Discussionmentioning
confidence: 85%
“…The risk of childhood asthma in infants living in the highest urbanization level was higher than that in infants residing in the lowest urbanization level (OR, 1.26; 95% CI, 1.24–1.29; p < 0.0001). In a previous study, the risk of asthma or AR is higher in children living in rural areas than in urban areas ( 25 ). The lower prevalence of childhood asthma in children living in farms is associated with asthma-protective “farm effect” ( 26 ).…”
Section: Discussionmentioning
confidence: 85%
“…A 2015 study conducted on college students with a 58.5% prevalence of allergic rhinitis also reported lower quality of life. 19,20 The same thing is supported by studies conducted in Korea on adults who reported the impact of allergic rhinitis on the physical health of sufferers, which stated that the symptoms of allergic rhinitis had an adverse effect on sleep, daily activities, physical status, mental and social function. Allergic rhinitis sufferers also experienced fatigue, headaches, mood and sleep disorders, physical disturbances, mental problems, and cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 86%
“…Allergic rhinitis is a very common disease that impairs quality of life if left untreated. Although the prevalence of allergic rhinitis is between 10% and 58,5% worldwide, it varies widely [2]. Allergic rhinitis is an immunoglobulin E (IgE) mediated allergic disease.…”
Section: Allergic Rhinitismentioning
confidence: 99%